Integration of Culture and Islam in Learning Mathematics in The Independent Curriculum - Nuryami; Yulina Fadilah (Kirana Publisher (KNPub), 2023)
Learning mathematics must experience changes in the context of improving the quality of education to improve optimal learning outcomes. Therefore, efforts continue to be made to realize innovative learning following the times and technology. In addition to harmonizing education with technological advances, education is also expected to build the values ​​and character of each student through local culture and religious values. The integration of mathematics with Islamic values ​​and local cultural wisdom developed through exploratory literature. This paper presents the idea of ​​formulating a method for integrating mathematics with local culture and integrating mathematics with religious values. This integration aims to make students more familiar with local cultures and motivate them to learn mathematics. The integration of mathematics with religious values ​​seeks to provide an overview of the interpretation of several verses of the Qur'an related to faith, which are then integrated into discussions in mathematics.